Sikap Remaja Putri tentang Kanker Serviks dengan Motivasi Remaja Melakukan Vaksinasi HPV - Putu Indah Sintya Dewi; Luh Ayu Purnami; Mochamad Heri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the relationship between the level of knowledge and attitudes of adolescents about cervical cancer with the motivation of adolescents to vaccinate against HPV at SMA Negeri 1 Ubud. This type of research is a quantitative study with an analytic research design with a cross sectional approach, the sample in this study was 97 respondents with proportional simple random sampling technique. The results of the univariate analysis of most of the respondents, most of the students had a sufficient level of knowledge about cervical cancer, 41 respondents (42.3%), 59 students had a supportive attitude about cervical cancer (60.8%) and students had moderate motivation to do the HPV vaccination as many as 71 children ( 73.2%). The results of this study showed that 35 students had sufficient knowledge of cervical cancer and moderate motivation to vaccinate against HPV (36.1%). The results of the Spearman Rank test analysis of students have a supportive attitude about cervical cancer and moderate motivation to vaccinate HPV by calculating the calculated r value of 0.279 and a probability of 0.006 (0.006 <0.05). In conclusion, there is a significant relationship between the variable attitudes of adolescents about cervical cancer with the motivation of the eleventh class of SMA Negeri 1 Ubud to vaccinate against HPV. Keywords : Knowledge, attitude, cervical cancer, motivation